Kolaborasi Strategi Branding Produk Oreo X Blackpink Melalui Pemanfaatan Popularitas Blackpink - Novi Tri Oktavia; Risqika Yunafiroh; Agus Eko Sujianto; Mashudi Mashudi; Dwi Astuti Wahyu Nurhayati (JURNAL ILMIAH EDUNOMIKA, 2023)
Creating new product brings big impact to be rejected by the market because most of societies have not known yet the brand product. One of the strategies which can be done the manufacturer is by conducting collaboration with other products to attract the public’s interest in buying rate today, instead of other effort. In this case, the researcher intends to conduct a study related to the collaboration with other products which is often done by Oreo Biscuit products. This research deploys the descriptive qualitative approach by applying the case study method. The sample of the research was 33 respondents. The result of this study was collaboration product which was done with Oreo Biscuit product and Blackpink Girl Band, this collaborative working could be accepted successfully in the market especially most of the society who become Black pink Girl Band, they want to get Oreo X Black pink enthusiastically. Not only must a few of consumers wait for getting the product of Oreo X Black pink because this product was sold fast even though products of Oreo X Blackpink were displayed in the shelves of minimarket, supermarket, or social media.